Performance Test of K0-NAA and Relative Method for Analysis of Al, Mg, K Nuclides in SRM Lake Sediment Sample - Sunardi Sunardi; Darsono Darsono (Universitas Gadjah Mada, 2017)
A performance test has been conducted of k0-NAA and relative methods for analysis of Al, Mg, K nuclides in SRM lake sediment sample (SRM SL-3). The performance test included validation, accuracy and precision tests, as well as t and F test. This test is done in order to know the performance of the both methods. Test results on validation test of both the k0-NAA and relative methods obtained were still in good performance with z-score values within the range of -2 ≤ x ≤ 2, in the accuracy and precision test showed that the two methods used were still reliable or passed the test for elemental analysis. The results of the evaluation t-test were at 95% confidence level showed that both methods were no significant differences in the test results, and the evaluating the F test showed that there are no differences in the accuracy between the two methods. The performance test data are expected to be used by practitioners and users of neutron activation analysis services as the reference option of analysis method to optimize the objectives to be achieved.